An overview of medicinal plants as wound healers - Prafulla Sabale, Bhargav Bhimani, Chirag Prajapati and Vidya Sabalea (Journal of Applied Pharmaceutical Science)
Wound healing is an integrated cellular and biochemical process of restoring normal structure functions of damaged tissue. Healing is a natural phenomenon by which body itself overcome the damaged to the tissue but the rate of healing is very slow and chance of microbial infection is high. Improvement in healing process can be accomplish either shorten the time required for healing or to minimize the undesired consequences. India has a rich tradition of plant-based knowledge on healthcare system. Several herbs and medicinal plants proved to be a wound healers were identified and formulated for treatment and management of wounds. Various herbal products have been used in management and treatment of wounds over the years. The present review attempt to highlight some herbs and medicinal plants proved to be scientifically used for the treatment of cuts and wounds as a wound healer.
Keywords: Wound, Wound infections, Wound healers, Wound healing activity, Wound healing medicinal plants.